Pregnancy Outcomes among Adolescents and Young Adults with Diabetes in Kumasi, Ghana - Ameyaw, Emmanuel; Asafo-Agyei, Serwah Bonsu; Hammond, Charles Kumi; Nguah, Samuel Blay; Damalie, Francis Jojo Kwadzo; Senaya, Charles Mawunyo; Adutwum, Laila Matogah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Pregnancy in patients with diabetes is known to be associated with complications. Improving glycaemic control can improve pregnancy outcomes. Aims: This study assessed pregnancy outcomes among adolescents and young women with diabetes at Paediatric and Adolescent Diabetes Clinic, Komfo Anokye Teaching Hospital, Kumasi, Ghana. Methods: A clinical review involving eighteen children and young women with diabetes who became pregnant during follow-up care at Paediatric and Adolescent Diabetes Clinic in Ghana. Girls and young women suspected to be pregnant were referred to antenatal clinic for confirmation. Multidisciplinary care including comprehensive antenatal care was given to each participant throughout the pregnancy. Questionnaire was used to gather demographic and clinical information of participants including pregnancy outcomes. Results: A total of eighteen adolescents and young women got pregnant and were included in the study. They were attending school when they got pregnant, 55.6% were in Senior High School, 33.3% were in Junior High School and 11.1% were in Teacher Training College. The mean age at pregnancy was 18.39 years (SD 2.97). Two pregnancies ended in abortion while 16 resulted in 18 live births (14 singleton and 2 twin deliveries). All deliveries were supervised, 56.3% delivered via cesarean section. Two births were preterm, occurring at 30 and 32 weeks of gestation. Neonatal outcomes were generally favorable: all babies were clinically well, 55.6% had 5-minute APGAR (Appearance, Pulse, Grimace, Activity, and Respiration) score between 8 and 10, while 44.4% had 5-minute APGAR score between 6 and 7. Only one infant (5.6%) had a congenital malformation. One baby died at one month due to septicemia. Conclusion: Structured multidisciplinary interventions led to positive pregnancy outcomes among young females with diabetes in Ghana.